Energy system efficiency in Cuba de composition analysis of energy use and co2 emissions - Jarmo Vehmas; Jyrki Luukkanen; Anaely Saunders Vázquez; Jari Kaivo-oja (Revista Científica de Ingeniería Energética, 2023)
This article presents results from a decomposition analysis of energy consumption and CO2 emissions in Cuba during the period 1971–2019. Energy decomposition is done with a dynamic Sun-Shapley decomposition, which produces activity, intensity, and structural effects. CO2 decomposition has been done with a chained two-factor decomposition, which provides effects identified in an extended Kaya identity. The results show that during this period, changes in sectoral energy intensities and the economic structure have decreased energy consumption slightly more than economic growth has increased it, but CO2 emissions have not decreased correspondingly because of economic growth per capita and increasing carbon intensity of the primary energy mix. These kinds of scientific findings indicate that the energy efficiency policy in Cuba requires some more attention.